Sexual identity: effeminacy among university students - Mohd. Noor, Noraini; Farooqui, Jamil; Muhammad Nasr, Ahmad Abd Al-Rahim; Md. Noon, Hazizan; Abd Rahman, Shukran (IIUM Press, 2005)
The study focuses on the effeminate male students of the university. The phenomenon of effeminate male students on some university campusses has become a matter of concern. It is presumably the first study of such students at an institution of higher learning. It started before this issue became a subject of debate in newspapers. The study consists of an introduction; three chapters on empirical findings pertaining to students' perceptions of effeminate male students, the psychological profile of effeminates in comparison to normal male and female students, and qualitative interviews with both the effeminates and their friends; a conclusion and seven appendices. The experts attributed sexual identity disorder to the influence of nature and nurture. They distinguished between the genetically effeminate males and those who deliberately become effeminates. It is latter that should be guided in order to eliminate their sexual identity confusion and protect the society.